Knowledge and confidence of Australian emergency department clinicians in managing patients with mental health-related presentations: findings from a national qualitative study - Jelinek, George A (Springer, 2013)
BACKGROUND: Mental health related presentations are common in Australian Emergency Departments (EDs). We sought to better understand ED staff knowledge and levels of confidence in treating people with mental health related problems using qualitative methods. METHODS: This was a qualitative learning needs analysis of Australian emergency doctors and nurses regarding the assessment and management of mental health presentations. Participants were selected for semi-structured telephone interview using criterion-based sampling. Recruitment was via the Australasian College for Emergency Medicine and College of Emergency Nursing Australasia membership databases. Interviews were audio-recorded and transcribed verbatim. Thematic framework analysis was used to identify perceived knowledge gaps and levels of confidence among participants in assessing and managing patients attending EDs with mental health presentations. RESULTS: Thirty-six staff comprising 20 doctors and 16 nurses consented to participate. Data saturation was achieved for four major areas where knowledge gaps were reported. These were: assessment (risk assessment and assessment of mental status), management (psychotherapeutic skills, ongoing management, medication management and behaviour management), training (curriculum and rotations), and application of mental health legislation. Participants’ confidence in assessing mental health patients was affected by environmental, staff, and patient related factors. Clinicians were keen to learn more about evidence based practice to provide better care for this patient group. Areas where clinicians felt the least confident were in the effective assessment and management of high risk behaviours, providing continuity of care, managing people with dual diagnosis, prescribing and effectively managing medications, assessing and managing child and adolescent mental health, and balancing the caseload in ED. CONCLUSION: Participants were most concerned about knowledge gaps in risk assessment, particularly for self-harming patients, violent and aggressive patients and their management, and distinguishing psychiatric from physical illness. Staff confidence was enhanced by better availability of skilled psychiatric support staff to assist in clinical decision-making for complex cases and via the provision of a safe ED environment. Strategies to enhance the care of patients with mental health presentations in Australian emergency departments should address these gaps in knowledge and confidence.